ECONOMIC DEVELOPMENT AND STATE FINANCIAL POLICIES AS A RELATED CATEGORY: CONTENT AND MAIN CONCEPTS - Романчукевич, Віталій (Socio-economic relations in the digital society, 2019)
The scientific approaches to the interpretation of the concept of «financial policy» are considered. It is revealed that the improvement and modernization of the fi nancial policy of the state, on which the formation and distribution of financial resources of all subjects of economic relations depends, should be conducted taking into account the peculiarities of the interaction of these subjects. It is proved that in the present conditions the state of the category «state financial policy» and «economic development» are mutually interconnected and interconnected. It was noted that foreign science and practice emphasize the fi nancial policy of business entities, while in Ukraine it is based on state financial policy. It is revealed that most scientifi c approaches to the interpretation of the term «financial policy» make an eff ort to achieve a certain level of economic development. The approaches to understanding by scientists of the defi nition of «economic development» and discovered that in spite of the lack of a unifi ed approach to understanding the concept of «economic development» and the presence of a considerable number of diff erent author’s approaches, all of them (both Ukrainian and foreign sources) basically contain two main factors: a qualitative improvement in the process of creating an economic good and the direction of the whole process to improve the living standards of the population, his prosperity. The views of leading scientists of the West of the twentieth century are highlighted. on state interference in the economy. The main tasks of fi nancial policy and types of fi nancial policy depending on the tasks solved in the society are considered. Th e main types and types of fi nancial policy are revealed. It is generalized that financial policy is a complex socio-economic phenomenon, a set of various measures aimed at optimal formation, distribution and use of financial resources in order to achieve a certain level of economic development. The nature, type and type of fi nancial policy depend on the conditions in which it is implemented (including the volume of fi nancial resources in the state) and the level of economic development that is planned to be achieved.